THE INFLUENCE OF SOCIAL STRATIFICATION ON ACCESS TO INCLUSIVE EDUCATION IN INDONESIA - Mujahidin Mujahidin (Indonesian Journal of Education (INJOE), 2025)
This study analyses the influence of social stratification on access to inclusive education in Indonesia, where economic, geographical, and cultural inequalities are major barriers for children with special needs from vulnerable groups. Using a descriptive qualitative approach with literature studies and secondary data analysis from journals and Ministry of Education and Culture policies, the findings show that poor families in rural areas experience low participation due to high costs, lack of infrastructure, and social stigma, despite regulations such as the National Education Law. The implications weaken social mobility and inclusive human resource development; recommendations include proportional budget allocation, massive teacher training, and anti-discrimination campaigns for equitable access to education.